Analysis of Stress State and Damage Characteristics of the Cement Sheath - Xu, Feng; Ren, Qingyang; Ling, Hao; Yin, Hongwu; Zhou, Xiaogui; Liu, Zhongshuai; Yang, Guangqing (Frontiers in Energy Research, 2022)
The sealing problem of cement sheath often appears in gas wells for underground energy exploitation, especially when horizontal multi-stage fracturing technology is used in the shale gas industry. In this paper, according to the elastic-plastic mechanics and Mohr-Coulomb yield criteria, an analytical solution of the equations is obtained by considering the effect of pressure in the fluid column, volume shrinkage or expansion and geological characteristics on the initial stress of cement sheath. The analysis of the example indicates that the smaller the initial stress of cement sheath is, the lower its radial stress and circumferential stress, which is under the maximum inner casing pressure of 150MPa. With the increase of initial stress of cement sheath, it's easier for the first and second interfaces to enter the plastic and damage state for cement sheath. The smaller the initial stress of the cement sheath, the earlier damage appears and it develops with the increase of inner casing pressure more quickly. When the initial stress of cement sheath is less than 7.9MPa, the damage factor finally reaches 1 with the increase of internal casing pressure; However, when the initial stress of cement sheath is greater than 34.2MPa, the damage factor always keeps 0 with the increase inner casing pressure. The results preliminarily revealed that the initial stress of cement sheath plays a decisive role in promoting its integrity and may provide guidance for the choice of the formula of cement and construction methods in the oil field.